Global Discussion on Life Cycle Assessment Allocation Methods for Recycled Fibers - Ivana Azuaje; Ronalds Gonzalez; Tomas Ekvall; Caroline Gaudreault; Luana Dessbesell; Qingshi Tu; Erlantz Lizundia (BioResources)
On September 3rd, 2024, North Carolina State University, the University of British Columbia, Aalto University, the University of Chile, and the University of the Basque Country organized a global webinar on allocation methods for recycled fibers. The event focused on the challenges and complexities associated with allocation methods for open-loop recycling systems, focusing on bio-based fibers for packaging. The webinar featured three expert presentations by Dr. Tomas Ekvall, Dr. Caroline Gaudreault, and MSc. Ivana Azuaje, each offering valuable insights into the topic.